TEKNIK SCROLL UNTUK PEMBUATAN PRODUK INTERIOR - Andono Andono; Aruman Aruman (Corak : Jurnal Seni Kriya, 2013)
In the world of crafts, especially wood craft, some techniques have been known to createa work of art such as carving, lathing, scrolling, etc. Scroll technique is the work of wood craftproduction using scrolling tools such as scrollsaw, which is a saw with small ribbon powered byelectricity. The tool has the specifications of cutting perpendicular, oblique, straight, and curvedpositions. This device is usually used as a tool to make holes in the process of wood carving(krawangan), or to cut the carving edge. In addition, scroll saw is usually used to make puzzle(education props / toys), and letters.With its specifications, scrollsaw can be explored further by making it as a major tool in themanufacture of wood craft art, such as interior elements. Our preliminary research proved thatthe tool can be used as the main tool for the manufacture of wood craftsmanship products(decorative masks) that is unique and distinctive. So in this study we try scroll technique for themanufacture of some products for interior elements, such as mirrors, wall clocks, table / walllamps, and the flowerpots. The manufacturing process consists of some stages such asexplorating, designing, embodying, and evaluating. By exploring the scroll technique, planks ofwood that are cut will produce a curved piece and form a small square field. If the blades arearranged with the arrangement that is designed with a particular composition, they will bear acertain distinctive and unique motive form in their field surface. The product of the interiorelements will have distinctiveness, uniqueness, and attractiveness of their own.Scroll technique can be developed for the manufacture of art craft products because thescrollsaw is easy enough to use. Therefore, this scroll technique can be used as a new jobopportunity for people who want to be engaged in it to reduce the number of unemployedpeople. Being creative with the scroll technique can be engaged professionally or just as ahobby for works of art. Keywords: scroll techniques, craft product, interior elements